Cape Nome Stores - Howard, Mart Albert, 1855-1926 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Lantern Slide: b&w; 10 x 8 cm. Storefronts and boardwalk in Cape Nome, a Gold Rush in Alaska and Yukon Territory history second only to the Klondike in terms of popularity and prospectors drawn and lasted from 1899-1909.